Discovery of witches Season 2 - Goode, Matthew, 1978-; Palmer, Teresa, 1986-; Aird, Holly, 1969-; Bluemel, Edward, 1993-; Buska, Malin, 1984-; Chillin, Gregg, 1988-; Cree, Steven; Cusack, Sorcha, 1949-; Ezra, Daniel; Gravelle, Trystan, 1981-; Hale, Amanda, 1982-; Hart, Aiysha; et al. (Chatsworth, CA Image Entertainment, 2021)
Having escaped to hide in Elizabethan London, Matthew and Diana must find a powerful witch teacher to help Diana control her magic and search for the elusive Book of Life. Enemies are everywhere, the threat to witches is growing, and Diana and Matthew's romance faces a barrage of new threats, from within as much as without.
Disc 1. Episodes 1-5 -- Disc 2. Episodes 6-10 ; Bonus features.
Title from disc surface.
Based on the the All souls trilogy by Deborah Harkness.
Originally broadcast as single episodes of a television program in 2021.
Wide screen.
Bonus features: The story of "A Discovery of Witches" ; Can love survive ; Creating Elizabethan London.
Matthew Goode, Teresa Palmer, Holly Aird, Edward Bluemel, Malin Buska, Gregg Chillin, Steven Cree, Sorcha Cusack, Daniel Ezra, Trystan Gravelle, Amanda Hale, Aiysha Hart, Tom Hughes, Jacob Ifan, Adelle Leonce, Michael Lindall, Aisling Loftus, Tanya Moodie, Valarie Pettiford, Adrian Rawlins, Elaine Cassidy, Sheila Hancock, Michael Jibson, Anton Lesser, James Purefoy, Paul Rhys, Trevor Eve, Owen Teale.
Keywords: Vampires -- Drama; Witches -- Drama; Alchemy -- Manuscripts -- Drama; Science and magic -- Drama; Man-woman relationships -- Drama; DVD-Video discs; Drama; Fantasy television programs; Fiction television programs; Paranormal television programs; Television programs; Video recordings for the hearing impaired